Antagonism of the chemokine Ccl5 ameliorates experimental liver fibrosis in mice - Berres, Marie-Luise; Koenen, Rory R.; Rueland, Anna; Zaldivar, Mirko Moreno; Heinrichs, Daniel; Sahin, Hacer; Schmitz, Petra; Streetz, Konrad L.; Berg, Thomas; Gassler, Nikolaus; Weiskirchen, Ralf; Proudfoot, Amanda; et al. (The Journal of Clinical Investigation, 2010)
Activation of hepatic stellate cells in response to chronic inflammation represents a crucial step in the development of liver fibrosis. However, the molecules involved in the interaction between immune cells and stellate cells remain obscure. Herein, we identify the chemokine CCL5 (also known as RANTES), which is induced in murine and human liver after injury, as a central mediator of this interaction. First, we showed in patients with liver fibrosis that CCL5 haplotypes and intrahepatic CCL5 mRNA expression were associated with severe liver fibrosis. Consistent with this, we detected Ccl5 mRNA and CCL5 protein in 2 mouse models of liver fibrosis, induced by either injection of carbon tetrachloride (CCl4) or feeding on a methionine and choline–deficient (MCD) diet. In these models, Ccl5–/– mice exhibited decreased hepatic fibrosis, with reduced stellate cell activation and immune cell infiltration. Transplantation of Ccl5-deficient bone marrow into WT recipients attenuated liver fibrosis, identifying infiltrating hematopoietic cells as the main source of Ccl5. We then showed that treatment with the CCL5 receptor antagonist Met-CCL5 inhibited cultured stellate cell migration, proliferation, and chemokine and collagen secretion. Importantly, in vivo administration of Met-CCL5 greatly ameliorated liver fibrosis in mice and was able to accelerate fibrosis regression. Our results define a successful therapeutic approach to reduce experimental liver fibrosis by antagonizing Ccl5 receptors.